Intracranial self-stimulation reward thresholds during morphine withdrawal in rats bred for high (HiS) and low (LoS) saccharin intake - Holtz, Nathan A. (Brain Res, 2015)
RATIONAL: Sweet preference is a marker of vulnerability to substance use disorders, and rats selectively bred for high (HiS) vs. low saccharin (LoS) intake display potentiated drug-seeking behaviors. Recent work indicated that LoS rats were more responsive to the negative effects of drugs in several assays. OBJECTIVE: The current study used the intracranial self-stimulation (ICSS) procedure to investigate the anhedonic component of morphine withdrawal in male HiS and LoS rats. METHODS: Rats were administered morphine (10 mg/kg) or saline for 8 days. To evaluate withdrawal effects, reward thresholds were measured 24 and 28 h following the 8(th) morphine injection (spontaneous withdrawal) and again for 4 days following daily acute morphine and naloxone (1 mg/kg) administration (precipitated withdrawal). RESULTS: Twenty-four hr following the final morphine injection, reward thresholds in LoS rats were significantly elevated compared to reward thresholds in LoS controls, indicating spontaneous withdrawal. This effect was not observed in HiS rats. LoS rats also showed greater elevations of reward thresholds on several days during naloxone-precipitated withdrawal compared to their HiS counterparts. CONCLUSIONS: LoS rats were more sensitive to morphine withdrawal-mediated elevations in ICSS thresholds than HiS rats. While these differences were generally modest, our data suggest that severity of the negative affective component of opiate withdrawal may be influenced by genotypes related to addiction vulnerability.